Wyszukana prawda. Józef Pankiewicz o sztuce w kontekście malarskiego warsztatu - Wachowiak, Mirosław (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
Pankiewicz as conscious artist of his time was absorbing achievements of innovative movements appearing throughout his life. Yet he was critical and did choose sources of inspirations selectively. Some traditional elements of the work of art as proportion expressed with proper drawing, or homogenous, balanced and united composition as well as space gained with the light and shadow did still matter for him. On the other hand he admired colourful interaction, simultaneous contrast and musical harmonies of the perfectly juxtaposed hues. His art can be characterised by pairs of oppositions like truth, but refined, nature observed but in the same time felt with emotion, the joy of painting but controlled with conscious will, proceeding rationally to the final effect. He treated very seriously also the technical part of work using high quality materials and studying Old Masters to learn methods of solution of formal and technological problems. Lack of technological knowledge and practical workshop practice seems for Pankiewicz to be the source of many problems of the “young art.” Yet tradition did not close him on new propositions of avant-garde and especially of colouristic achievements. Defining in the modern way work of art at first as decorative surface giving joy to the eyes he did not resigned from nature as source of main inspiration. His art continuously evolving kept its solidness by creative dialogue of old and new confronted with strict clear sight directed to visible reality and softened by delight with colour. Inspired with Cézanne and his words on the unity of the drawing and colour, he was going his own path faithful to nature seen with the fresh eye of the joyful but conscious colourist.